Research on the influence of employee psychological capital and knowledge sharing on breakthrough innovation performance - Liu, Yuhan; Chen, Jianbin; Han, Xiaolei (Frontiers in Psychology, 2023)
Breakthrough innovation is the focus of the society in the era of knowledge economy. Employee innovation of the enterprises is the starting point of enterprise innovation behavior,and it is the result of the combination of complex psychological capital. Meanwhile, breakthrough innovation often comes from the result of knowledge sharing brought by teamwork.At present , existing studies mainly reveal the influence of psychological capital and psychological capital structure on the breakthrough innovation performance. However, the relationship between psychological capital, knowledge sharing and the breakthrough innovation performance needs to be systematically studied.Therefore, this study adopted a mixed research approach, that is, statistical analyses were performed by using SPSS Version 18 and AMOS version 26 (Statistical analyses performed by using SPSS Version 18 and AMOS version 26). This study collected data on employees of 345 different new high-tech enterprises to explore the mechanism by which psychological capital and knowledge sharing affects the breakthrough innovation performance. The research results respond to a positive correlation between psychological capital and knowledge sharing affects the breakthrough innovation performance. Moreover, knowledge sharing has a mediating effect on the effect of psychological capital on breakthrough innovation performance, and the effect is weakened.which is of great theoretical significance for exploring the relationship between psychological capital and knowledge sharing affects the breakthrough innovation performance.